THE CHARACTERISTICS OF INTERNATIONAL AND HUNGARIAN TALENT SHORTAGE - MÃ¡ria HÃ©der; Krisztina Dajnoki (Annals of the University of Oradea: Economic Science, 2017)
The current challenge of the labour market is the labour shortage appearing even on a global level. Nowadays the majority of employers face this problem the handling of which has become one of the central tasks of a human resource manager besides keeping the employees. The appearance of labour shortage is realised on different levels in the market (expert shortage, knowledge shortage, skilled worker shortage etc.) of which the latest approach is the lack of talented employees. It is vital to define precisely and interpret the problem in order to tackle it effectively. The research relied on Hungarian and international literature to provide an answer to the right definition of talented employee and the lack of it. The appearance of talent shortage cannot be connected to a single state but it can be looked upon as globally extensive. The most thorough mapping of the talented employee shortage on an international level has been done by a Manpower Group research with the help of which we can receive detailed information about the global scales and the tendencies experienced in the measured countries. The results of the research draw conclusions from the difficulties of filling positions highlighting the scale of talented employee shortage in the countries measured. We are given an answer to which professional fields are the most difficult to find the right employee for. It also reveals what difficulties the employers are facing and how they try to handle the problem. The study introduces a few targeted solution strategies to manage talent shortage based on literature and Manpower expert recommendations. The need for excellent people has undoubtedly become one of the most pressing economic questions which requires a targeted solution as soon as possible. To make this happen if would be useful to do a research which specifically reveals the Hungarian peculiarities which can interpret the question country-specific thus could provide a more efficient help to shape a solution strategy.